2020
DOI: 10.1002/vms3.282
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of 4 commercial modified‐live porcine reproductive and respiratory syndrome virus (PRRSV) vaccines against heterologous dual Korean PRRSV‐1 and PRRSV‐2 challenge

Abstract: Background Four commercial porcine reproductive and respiratory syndrome virus (PRRSV) modified‐live vaccines (MLV) was compared to protect growing pigs against dual challenge of PRRSV‐1 and PRRSV‐2. Methods Two of the vaccines were based on PRRSV‐1, and two on PRRSV‐2. A total of 72 PRRSV‐naïve pigs were divided into six groups (12 pigs/group). Results Two PRRSV‐1 MLV‐vaccinated and two PRRSV‐2 MLV‐vaccinated groups reduced significantly (p < .05) genomic copies of PRRSV‐1 in their sera compared to the unvacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…According to one farm owner's description, the outbreak of PRRS due to NADC30-like infections in a farrowfinish farm with a 2,000-sow inventory resulted in over 2 million RMB losses in 2020. The Ingelvac PRRS R MLV vaccine has been shown to provide cross-protection against over 10 genetically diverse PRRSV isolates, including several fieldisolated NADC30-like strains currently circulating in China (26,(28)(29)(30)(40)(41)(42). However, compared with homologous protection, lower protection was observed in the heterologous challenge groups (19).…”
Section: Discussionmentioning
confidence: 99%
“…According to one farm owner's description, the outbreak of PRRS due to NADC30-like infections in a farrowfinish farm with a 2,000-sow inventory resulted in over 2 million RMB losses in 2020. The Ingelvac PRRS R MLV vaccine has been shown to provide cross-protection against over 10 genetically diverse PRRSV isolates, including several fieldisolated NADC30-like strains currently circulating in China (26,(28)(29)(30)(40)(41)(42). However, compared with homologous protection, lower protection was observed in the heterologous challenge groups (19).…”
Section: Discussionmentioning
confidence: 99%
“…PRRSV-2 isolate, and cross-protection between PRRSV-1 and PRRSV-2 is considered insignificant, as demonstrated in different studies carried out in adult sows (38,39), boars (40,41), and piglets (42,43). This is probably due to the enormous genetic divergence between the two PRRSV species (14).…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be mentioned that the characteristics of the PRRSV isolates used for the secondary exposure in some of those groups might have also contributed to the outcome of infection. Thus, the pigs of group A.2 were exposed to a PRRSV-2 isolate, and cross-protection between PRRSV-1 and PRRSV-2 is considered insignificant, as demonstrated in different studies carried out in adult sows ( 38 , 39 ), boars ( 40 , 41 ), and piglets ( 42 , 43 ). This is probably due to the enormous genetic divergence between the two PRRSV species ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the individual level, MLV vaccination usually cannot induce sterilizing immunity to completely block the infection of heterologous strains [ 75 , 104 , 105 , 106 , 107 ]. However, many experimental vaccination-challenge trials or field studies have indicated that PRRSV vaccination can provide partial protection against heterologous strains, shown as delaying the onset of viremia, reducing the duration of viral shedding and significantly decreasing viral load throughout infection, not showing severe clinical signs as unvaccinated animals [ 75 , 97 , 106 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ].…”
Section: Protection Efficacy Of Prrs MLVmentioning
confidence: 99%